A peat bog record of natural, pre-anthropogenic enrichments of trace elements in atmospheric aerosols since 12 370 14C yr BP, and their variation with Holocene climate change - Shotyk, William; Krachler, Michael; Martinez-Cortizas, Antonio; Cheburkin, Andriy K.; Emons, Hendrik (Earth and planetary science letters, 2002)
A peat bog in the Jura Mountains, Switzerland, provides a continuous record of peat accumulation since 12 370 14C yr BP. Periods of enhanced soil dust deposition (10 590 14C yr BP, 8230 14C yr BP, and after 5320 14C yr BP) are characterized by strongly elevated Ti/Sc and Zr/Sc ratios which imply an increase in the abundance (both relative and absolute) of heavy minerals such as ilmenite and zircon. With respect to trace elements such as Cu, Zn, As, Cd, Sb and Au, the M/Sc ratios are at their lowest, and often approach crustal values, during periods of enhanced soil dust deposition. The lowest rates of atmospheric deposition of soil dust date from 8030 to 5320 14C yr BP, corresponding to the Holocene climate optimum, but here many trace elements exhibit their greatest natural enrichments: the average enrichment factor (calculated using Sc as the reference element, and normalizing to crustal abundance) was Zn 4.1±1.4, Sb 4.8±1.4, Cu 8.8±3.3, As 14.9±3.2, Au 53.9±25.1, and Cd 357.4±53.8. These enrichments cannot be explained by chemical diagenesis within the deeper sections of the peat profile during or subsequent to peat formation, but rather reflect the chemical composition of airborne material supplied to the surface layers of the bog at the time of deposition. The enrichments of trace metals in ancient peats, relative to crustal abundance, most likely reflects the natural enrichment of these elements in the fine fraction of soils during rock weathering. Periods of enhanced soil dust deposition such as the Younger Dryas cold climate phase (10 590 14C yr BP) are characterized by reduced vegetation cover, greater exposed soil surface, and higher wind strengths; these conditions promote the transport of locally derived soil materials of greater particle size, lower concentration of trace metals, and M/Sc ratios approaching crustal values. During the Holocene climate optimum, vegetation cover was extensive, and with lower wind strengths and a reduction in erodible soil materials, long range transport of soil dust became relatively more important to the soil dust inventory of the bog; soil dust particles in this size class are characterized by strong enrichments of a wide range of trace elements. At the end of the Holocene optimum, dust fluxes increased once again, due mainly to soil erosion resulting from the combined effects of human activities (tillage) and the climatic deterioration at the beginning of the Neoglaciation Period; this promoted the supply of local, more coarse soil particles with M/Sc ratios approaching those of crustal rocks. While biological cycling and volcanic emissions probably also contributed to the atmospheric supply of many of these elements in the pre-anthropogenic past, these contributions appear to be less important than the chemical weathering, physical fractionation, and atmospheric transport of soil dust particles.
Im Titel ist die Ziffer "14" hochgestellt
Gesehen am 06.10.2020